STRATEGI PENYULUH AGAMA ISLAM DALAM MENINGKATKAN PELAKSANAAN SALAT WAJIB PADA MASYARAKAT DI TPA (TEMPAT PEMBUANGAN AKHIR) KELURAHAN TAMANGAPA KECAMATAN MANGGALA KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This paper aims to provide an explanation of the strategy of Islamic religious educators in increasing the implementation of obligatory prayers in the community at the TPA (final disposal site), through the efforts of Islamic religious educators in increasing the implementation of obligatory prayers, namely contributing to the construction of mosques in an environment that can be considered less clean and also held a grand Tabligh at the mosque around the TPA (Final Disposal Site) Tamangapa Village, Manggala District, Makassar City. The inhibiting factors experienced by Islamic religious instructors in improving the implementation of obligatory prayers are the lack of contribution from the community itself in participating in mosque activities, and some activities of the workers around the TPA (Final Disposal Site) which are too busy so that it inhibits Islamic religious instructors from entering into the community. location and provide guidance regarding obligatory prayers.